Enhanced reaching law for improved response in sliding mode control of PMSM motors with fuzzy logic integration - Truong, Khanh Quoc; Huynh, Son; Vo, Dung Hoang; Pham, Minh Duc (Institute of Advanced Engineering and Science, 2025)
The rising demand for high-performance permanent magnet synchronous motors (PMSMs) is responsible for the development of PMSM speed control. Although the proportional-integral controller is often used in field-oriented control (FOC) for motor speed regulation, it has drawbacks like slow response and instability. This paper proposed an enhanced sliding mode controller with a modified sliding surface to achieve better speed control performance. In comparison to proportional-integral or PI controller, fuzzy logic controller, conventional sliding mode controller, the proposed control approach uses a reaching law that incorporates a fuzzy logic controller. A smoother and faster response time is targeted by the proposed approach compared to conventional sliding mode control. Practical small-scale PMSM experiments certify the effectiveness of our proposed enhanced sliding mode control.